Optimization of HDI West Kalimantan with the Education Sector Effectiveness Strategy - Kurniawati, Dedek Kurniawati (Badan Penelitian dan Pengembangan Provinsi Kalimantan Barat, 2019)
The representation of optimal development outcomes is an effective education index. Besides, there are two components such as the health index and the purchasing power index which can also form the HDI. However, compared to the two components, the education index relatively affected the HDI, especially in West Kalimantan. Thus, it is expected that the effectiveness of education can be a solution to optimize HDI in other fields. Following the West Kalimantan Governor's program which focuses on providing free education as one of the supports in optimizing HDI in West Kalimantan. Also, increasing community participation in education development needs to be implemented. The application of accurate strategy as a solution to overcome problems in the education sector needs to be done optimally. Based on these efforts it is expected to answer various problems that exist in West Kalimantan, especially related to HDI in West Kalimantan.